Hard Red and Soft Red Winter Wheat Variety Testing - 2023 - Gretchen F. Sassenrath; Jane Lingenfelser; Xiaomao Lin (Kansas Agricultural Experiment Station Research Reports, 2023)
This is a summary of the winter wheat production conditions in southeast Kansas in 2021-2022 and the results of the winter wheat variety testing. Wheat production in 2022 benefited from dry conditions at flowering and harvest. Overall yields of hard red wheat were above multi-year averages, while soft red wheat yields were below the 15-year average. As in previous years, soft red winter wheat out-yielded hard red winter wheat varieties, but the extent was not as dramatic as in previous years.
Keywords: hard red winter wheat; soft red winter wheat; variety testing; southeast Kansas